Konsep pendidikan karakter Hasan Al-Banna dan relevansinya dengan pendidikan karakter di Indonesia - Muhibuddin Muhibuddin (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2022)
Character education is allegedly a solution to overcoming educational problems in Indonesia, which are increasingly worrying, especially the problem of juvenile delinquency and student moral decadence. One of the Islamic reformers who initiated character education was Hasan al-Banna. This study focuses on Hasan al-Banna's character education ideas and their relevance to the concept of character education in Indonesia. This library research focuses on Hasan al-Banna's works and is analyzed by Content Analysis and Phenomenology. Research shows that Hasan al-Banna applies character education by integrating the education system. Al-Banna seeks to integrate a dichotomous education system between religious education and general education. Hasan al-Banna's idea of ​​character education has relevance to the concept of character education in Indonesia. Its relevance lies in the idea that education must optimize all students' potential, namely faith, morals, reason, and body. Al-Banna's opinion is in line with the concept of character education in the 2013 curriculum, which aims to improve the process and results of quality education and is directed towards the formation of character and akhlakul karimah students in a comprehensive, integrated and balanced manner.